A critical review on visible-light-response CeO2-based photocatalysts with enhanced photooxidation of organic pollutants - Ma, Ran; Zhang, Sai; Wen, Tao; Gu, Pengcheng; Li, Lei; Zhao, Guixia; Niu, Fenlei; Huang, Qifei; Tang, Zhenwu; Wang, Xiangke (Catalysis today, 2019)
[Display omitted] •Design and preparation for visible-light-response CeO2-based photocatalysts are summarized.•Photodegradation mechanisms of CeO2-based photocatalysts are summarized and relevant recent works are reviewed.•The modified CeO2 exhibits high-performance photodegradation capacity of organic pollutants than pure CeO2. Organic pollutants’ treatment in wastewater has attracted extensive attention due to its degradation-resistance and potentially hazardous to human health. Some organic matters such as persistent organic pollutants (POPs) could exist in environment and resist to decomposition, which may cause chronic intoxication or even cancers. Because photocatalytic technique is efficient, nontoxic, and cost-effective to degrade organic pollutants, some semiconductors including TiO2 and ZnO as photocatalysts have aroused wide public concern. CeO2 has been reported as an efficient photocatalyst in contrast to TiO2 owing to its high oxygen storage, eco-friendly properties and photostability. But inefficient utilization of solar energy due to its intrinsic wide bandgap restrains its further application in real environmental pollutant treatment. In order to improve photocatalytic performances of CeO2, some modifications have been developed such as doping ions, coupling with semiconductor and construction of CeO2-based solid-solution. The purpose of this review is to introduce these techniques, reveals its fundamental mechanisms and the recent researches about photodegradation of organic pollutants in wastewater over CeO2-based photocatalysts. Besides, this review will evaluate the photocatalytic performance for organic pollutants and outlook the challenges and prospects in the future.